Experimental study on cavity pressure of carbon dioxide fracturing tube - Yongqing Zeng (JVE International, 2021)
The peak pressure and duration of high-pressure gas in the process of rock breaking by carbon dioxide fracturing will have a great impact on the fracturing effect of rock mass. For the sake of obtaining dynamic pressure response characteristic in the fracturing tube, the pressure-time curve of liquid CO2 blasting system was measured through several cavity pressure test of carbon dioxide fracturing tube. The cavity pressure test under different parameters of carbon dioxide quantity, activator quantity and thickness of energy release plate is carried out, in which TST6200 transient signal acquisition instrument, 109c12 type blasting shock wave sensor and special signal processing software system are used. The relation curve between pressure and time in the liquid CO2 fracturing tube was effectively measured and the variation law of pressure curve was analyzed. The results show that after igniting the liquid carbon dioxide fracturing tube, the cavity pressure rise slowly, then increases sharply and decays rapidly, when the pressure reaches the yield pressure limit of energy release plate, the energy release plate will be destroyed and high pressure gas will be released rapidly; the peak pressure in the CO2 fracturing system ranges from 169.1 MPa to 260.2 MPa, the duration of positive pressure is from 21.1 ms to 74.8 ms, and the peak pressure arrival time is between 13.2 ms and 67.7 ms. This paper attempts to establish the formula relationship between peak cavity pressure and thickness of energy release plate for carbon dioxide fracturing tube; the welded flat head formula, tensile failure formula and shear failure formula are used to calculate peak cavity pressure of carbon dioxide fracturing tube, in which the calculated results are compared with the measured values, the welded flat head formula severely underestimates the peak cavity pressure; conversely, the tensile failure formula slightly overestimated the peak cavity pressure; the shear failure formula can accurately reflect the peak cavity pressure of fracturing tube. The conclusions can be directly used for the design and optimization of fracturing tube by using different thickness energy release plate to control the cavity pressure of carbon dioxide fracturing tube.